STUDY OF THE PROCESS OF OBTAINING CALCIUM NITRATE - PRODUCTS OF NITRIC ACID DECOMPOSITION OF CALCIUM- CONTAINING SLUDGE - kizi, Dadakhanov Munisakhon Bakhodir; Mashrabboevich, Mamadaliyev Shukhrat; Makhammadzhanovich, Sobirov Mukhtorjon (The journal of contemporary issues in business and government, 2022)
It is known that calcium nitrate is an effective nitrogen fertilizer that provides high yields in all climatic and soil conditions. The effect of the application of calcium nitrate can be directly related to nitrate nitrogen and calcium in water, either separately, or in most cases as a combined action of these two nutrients. When calcium nitrate is obtained by decomposition of calcium-containing sludge from the water treatment plant of Farg’onaazot JSC with non-concentrated nitric acid (at least 57% HNO3), intensive, stable foaming is observed, which leads to a decrease in equipment productivity. When developing a technology for obtaining new types of suspended fertilizers based on calcium nitrate, the process of foaming during nitric acid processing of calcium- containing sludge was studied.